AB0766 The role of color-doppler-sonography in the diagnosis of giant cell arteritis characterized by adventitial inflammation of the temporal arteries. (23rd January 2014) - Francesco, M.; Boiardi, L.; Pipitone, N.; Cavazza, A.; Restuccia, G.; Germanò, G.; Macchioni, P.; Bajocchi, G.; Catanoso, M.G.; Magnani, L.; Rossi, F.; Chiarolanza, I.; et al.
Abstract : Background: The classic histological appearance of inflamed temporal arteries (TA) in giant cell arteritis (GCA) is transmural cell infiltration. However, periadventitial small vessel vasculitis (SVV) surrounding uninflamed TA and/or isolated vasculitis of the TA vasa vasorum (VVV) is found in a minority of patients with GCA. These patients have less frequently cranial manifestations and lower inflammatory markers at diagnosis compared to the patients with classic GCA, whereas the frequency of cranial ischemic events is similar (1). Color-doppler-sonography (CDS) can demonstrate a hypoechogenic (inflammatory) halo in the TA from patients with GCA in approximately 70% of cases. A study found a correlation between positive CDS findings and transmural inflammatory cell infiltration in GCA (2). There are no data on the performance of CDS in the diagnosis of SVV and/or VVV. Objectives: The aim of this study was to evaluate the prevalence of the characteristic halo sign in the TA from patients with SVV and/or VVV and to compare it with that found in patients with classic GCA. Methods: 30 consecutive patients with biopsy-proven SVV and/or VVV GCA who underwent CDS of the TA before TA biopsy were analyzed. Of this 30 patients, 16 had SVV, 11 isolated VVV, and 3 associated SVV and VVV. The identified patients were randomly matched to 30 biopsy-proven classic GCA patients. SVV was defined as aggregates of mononuclear inflammatory cells around capillaries located in the connective tissue surrounding the adventitia. VVV was defined as isolated vasculitis of TA vasa vasorum. A hypoechoic halo >0.4 mm around the TA lumen on CDS was considered diagnostic of GCA. For GCA categorization using the 1990 ACR criteria, SVV or isolated VVV were not considered to represent a positive TA biopsy. Results: Of the 30 patients with SVV and/or VVV-GCA 14 (46.6%) satisfied the ACR criteria for the classification of GCA. Table 1 shows the comparisons between the patients with SVV/VVV and classic GCA. Conclusions: The prevalence of the halo sign on CDS of the TA is significantly lower in patients with SVV/VVV-GCA compared with those with classic GCA. These results suggest that CDS does not perform well in these two subsets of GCA. TA biopsy is required to confirm the diagnosis of GCA in patients with SVV- and VVV-GCA. References: Restuccia G et al. Small-vessel vasculitis surrounding an uninflamed temporal artery and isolated vasa vasorum vasculits of the temporal artery: two subsets of giant cell arteritis. Arthritis Rheum. 2011 Sep 27. Schmidt D et al. Comparison between color duplex ultrasonography and histology of the temporal artery in cranial arteritis (giant cell arteritis). Eur J Med Res. 2003 Jan 28;8(1):1-7. Disclosure of Interest: None Declared